DC AND AC CONDUCTIVITY MEASUREMENTS OF Se60Te30Ge10 FILMS - Al-Haddad, Raad M; Ali, Iftikhar M; Ibrahim, Issam M; Al-Essa, Izzat M (Al-Nahrain Journal of Science, 2018)
D.c. σ(0) and a.c conductivity σ(w) and dielectric parameter ( and tan) of Se60Te30Ge10 glassy thin films which were prepared by thermal evaporation were investigated. Measurements of a.c. conductivity over frequency range (100Hz-100kHz) and temperature range (303-363K) showed that the a.c. conductivity follows the empirical formula a.c (w)=Aws, where (s) lies between (1.03-0.60).In the glasses of Se60Te30Ge10 thin films the d.c. conductivity along localized states prevails. A.c conductivity is explained by hopping mechanism of charge transfer between two defect centers.